2015
DOI: 10.1002/14651858.cd008106.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Surgical versus non-surgical interventions for treating patellar dislocation

Abstract: Background Patellar dislocation occurs when the patella disengages completely from the trochlear (femoral) groove. Following reduction of the dislocation, conservative (non-surgical) rehabilitation with physiotherapy may be used. Since recurrence of dislocation is common, some surgeons have advocated surgical intervention rather than non-surgical interventions. This is an update of a Cochrane review first published in 2011. Surgical versus non-surgical interventions for treating patellar dislocation (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
91
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(95 citation statements)
references
References 58 publications
2
91
0
2
Order By: Relevance
“…21 A recent Cochrane review of six studies with 344 participants found that participants managed surgically had a significantly lower risk of recurrent dislocation following first-time dislocation at 2 to 9 years of follow-up compared with those managed conservatively. 22 There were no differences in physical function scores. The authors, however, pointed out that the quality of evidence was very low because of the high risk of bias and the imprecision of the effect estimates.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…21 A recent Cochrane review of six studies with 344 participants found that participants managed surgically had a significantly lower risk of recurrent dislocation following first-time dislocation at 2 to 9 years of follow-up compared with those managed conservatively. 22 There were no differences in physical function scores. The authors, however, pointed out that the quality of evidence was very low because of the high risk of bias and the imprecision of the effect estimates.…”
Section: Discussionmentioning
confidence: 86%
“…The authors, however, pointed out that the quality of evidence was very low because of the high risk of bias and the imprecision of the effect estimates. 22 They recommended that adequately powered, multicentre, randomised controlled trials are needed to substantiate this evidence. 22 Erickson et al 23 carried out a systematic review of four metaanalyses on surgical treatment of first-time patellar dislocations.…”
Section: Discussionmentioning
confidence: 99%
“…Because the evidence in the literature is unsatisfying, no optimal treatment choice is available for this issue (18). Complexity of patellofemoral instability can make the decision of treatment more difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Functional rehabilitation is the mainstay of nonoperative management with particular focus on gait, core stability, and quadriceps strengthening [50]. A small number of older randomized trials comparing operative and nonoperative treatment of initial patellar dislocation found no benefit from immediate medial retinacular repair [51,52].…”
Section: Nonoperative Managementmentioning
confidence: 99%